Semi-Culture Phenomenon: Linguo-Communicative Aspect - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. At present, there is no doubt that during its historical development, different communities interact with one another or another, which necessarily implies parallelism of language contacts. Modern globalization processes require individuals to adapt to a rapidly changing socio-cultural environment, which implies the ability to interpret cultural phenomena in different linguistic and cultural contexts. Particular attention should be paid to the analysis of the communicative competence of the "interpreter", whose view on culture, its phenomena and forms of being determines the depth of understanding of historical realities and current practices. The aim is to analyze the phenomenon of semi-language as a negative consequence of cultural interference. The tasks are: 1) to characterize the situation of semi-language as an inconsistency or the imposition of one code of one language system on another in terms of intercultural communication; 2) to investigate the peculiarities of the loss of linguistic normality at the macro- and micro- levels. Research methods used in the article, reflect its interdisciplinary character. Research methods include proper linguistic and philosophical methods of analysis. The system-cultural, typological approaches are used in the research. Research results: analysis of the linguistic situation in modern society suggests that no bilingual bearer can have absolutely equal experience of contact with different linguistic groups, because, using certain words, he cannot control the social context. Semi-culture, as we understand it here, is a conflict situation in which the individual finds himself as a result of breaking the tradition. In favorable circumstances, a "semi-cultural" situation is temporal, and in unfavorable circumstances, it becomes a permanent factor, which can lead an individual to become a semi-linguistic one. Semi-language is the inability of an individual who has grown up in a bilingual environment to express his or her thoughts clearly in any language, to adhere to linguistic norms. Insufficient language development is not the only one that threatens the individual in the context of forced bilingualism. The specificity of voluntare (based on contract, consensus, dialogue) communication implies a reflexive interconnection of its subjects. Discussion. The lack of linguistic communication competence of native speakers undermines the rational form of organization of public space, which presupposes the achievement of public consensus. The extent to which the peoples are able to cope with this task is a serious question. Conclusion. Analysis of intercultural communication suggests that differences in culture and language of social groups in contact give rise to the phenomenon of semi-culture as a state of forced existence of personality in two cultures. The functioning of a semi-culture generates a semi-language with the rejection of stylistic, etiquette, etc. norms of differentiation of codes of different language systems. Micro-level code mixing manifests itself in the loss of the linguistic-communicative register, which is easily accessible to the developed "linguistic personality". Macro-level integration processes under half-life conditions lead to the formation of a reduced rather than a single and enriched culture. Semi-formalism in the formal presence of democratic institutions counteracts dialogue practices as the most cooperative form of communicative interaction based on reflective role-sharing.